Care preferences of older migrants and minority ethnic groups with various care needs: A scoping review - Viktoria Peters-Nehrenheim; Mike Rommerskirch-Manietta; Hürrem Tezcan-Güntekin; Martina Roes (PLoS ONE, 2026)
Background Older migrants and people from minority ethnic groups face unique challenges in accessing healthcare. Various factors often lead to lower healthcare utilization and hinder person-centered care. However, little is known about the various care preferences of these people, and no systematic overview of their care preferences has been conducted. Methods We conducted a scoping review in accordance with the description provided by the Joanna Briggs Institute. We searched the MEDLINE, CINAHL, PsycINFO, and Cochrane Library databases and extracted data from the included publications. We subsequently identified and analyzed the care preferences of older migrants and minority ethnic groups (people aged 60 years or older with various care needs) via inductive content analysis in an iterative process. Results Initially, 2756 records were identified through our electronic database search. After duplicate removal, 1924 records were screened for relevance. A total of 173 reports remained for full-text screening. A total of 50 studies published from 1985–2024 were included in the review. Our analysis of these articles revealed descriptive themes that were grouped into four main categories: I) care practice; II) professionals; III) living with others; and IV) environment. These main categories were further divided into 16 subcategories that captured the identified preferences. Conclusion Our research yielded two key findings. First, preferences related to care are as heterogeneous as the people receiving care. Second, people with dementia and a history of migration and their preferences in the nursing context, have been underrepresented in healthcare research. To bridge this knowledge gap, future research should prioritize understudied populations. By examining these groups, we can gain a more comprehensive understanding of the multifaceted individual experiences of older migrants and people from minority ethnic groups.